Discrete Multilinear Spherical Averages. Issue 2 (9th January 2019) - Cook, Brian
Abstract: In this note we give a characterization of $\ell ^{p}× … × \ell ^{p}→ \ell ^{q}$ boundedness of maximal operators associated with multilinear convolution averages over spheres in $\mathbb{Z}^{n}$ .